2014
DOI: 10.1186/s12888-014-0338-0
|View full text |Cite
|
Sign up to set email alerts
|

The household economic burden of eating disorders and adherence to treatment in Australia

Abstract: BackgroundThis study investigated the household economic burden of eating disorders and cost-related non-adherence to treatment in Australia.MethodsMulti-centre prospective observational study using a structured questionnaire. Ninety participants were recruited from two clinic settings in New South Wales, Australia and from the community using social media. The primary outcome measures were household economic burden of illness measured in terms of out-of-pocket expenditure, household economic hardship and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Eating disorders are severe and often chronic mental disorders that are associated with impaired cognitive and emotional functioning, restricted quality of life, lifelong physical and psychosocial morbidity, psychiatric comorbidity, and increased risk of mortality . In addition to the substantial individual and personal burden associated with eating disorders, the financial and economic impact of these illnesses is enormous . Although health care utilization among these individuals is elevated and evidence‐based treatments for eating disorders exist, a systematic review undertaken by Hart et al concluded that the pooled proportion of participants seeking treatment was 23.2% (95% CI = 16.6, 31.4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating disorders are severe and often chronic mental disorders that are associated with impaired cognitive and emotional functioning, restricted quality of life, lifelong physical and psychosocial morbidity, psychiatric comorbidity, and increased risk of mortality . In addition to the substantial individual and personal burden associated with eating disorders, the financial and economic impact of these illnesses is enormous . Although health care utilization among these individuals is elevated and evidence‐based treatments for eating disorders exist, a systematic review undertaken by Hart et al concluded that the pooled proportion of participants seeking treatment was 23.2% (95% CI = 16.6, 31.4).…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition to the substantial individual and personal burden associated with eating disorders, the financial and economic impact of these illnesses is enormous. 4,5 Although health care utilization among these individuals is elevated 6 and evidence-based treatments for eating disorders exist, 7-10 a systematic review undertaken by Hart et al 11 concluded that the pooled proportion of participants seeking treatment was 23.2% (95% CI 5 16.6, 31.4). However, variability in figures was reported in the review with proportions of participants seeking eating disorder treatment ranging from 0% in a study among middle school females 12 to 52% in a study among adult females with binge eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…One study from Australia investigated the household economic burden of eating disorders and cost-related nonadherence to treatment (Gatt et al, 2014). The primary outcome was the household economic burden of eating disorders measured using the following: out-ofpocket expenditure on medical and health-related expenses, household economic hardship (hardship hereafter), and cost-related non-adherence.…”
Section: Resultsmentioning
confidence: 99%
“…9 It was estimated that 914,000 people in Australia suffered from eating disorders in 2012. 10 The corresponding cost, including caring for the people suffering, was approximately $69 billion. 11 Different cultures and races have different definitions of beauty.…”
Section: The Connection Between Images Body Image and Eating Disomentioning
confidence: 99%